Water-stable aggregates and carbon accumulation in barren sandy soil depend on organic amendment method: A three-year field study. (1st March 2019) - Dai, Hongcui; Chen, Yuanquan; Liu, Kaichang; Li, Zongxin; Qian, Xin; Zang, Huadong; Yang, Xiaolei; Zhao, Yingxing; Shen, Yawen; Li, Zhejin; Sui, Peng
Abstract: Organic amendment has proven to reduce resource waste and environmental pollution, in addition to increasing soil quality. However, the effect of different organic amendment methods on water-stable aggregates and soil organic carbon (SOC) accumulation is unknown, especially in barren sandy soil. A field experiment with four organic amendment methods, straw (ST, local practice), biogas residue (BR), manure (PM), and biochar (BC), was designed with the equal amount of nitrogen (N) input in the North China Plain. Soil aggregate distribution, stability, and aggregate-associated C at two depths (0–10 cm and 10–20 cm) were analyzed after a treatment was applied to evaluate soil quality improvement. The main results were as follows: compared to ST treatment, BC treatment enhanced SOC in the 0–10 cm and 10–20 cm layers by 143.8% and 156.5%, respectively ( P < 0.05). The mean weight diameter (MWD) of soil aggregates in BR, PM, and BC treatments decreased by 16.2%–31.8%, 10.0%–24.7% (except the 2015 0–10 cm layer), and 18.9%–43.2% compared with ST treatment from 2014 to 2016. BC treatment increased C concentrations in all aggregate fractions compared to ST treatment in 2015–2016 ( P < 0.05). The correlations between soil microbial biomass C and MWD (R = 0.7185, P < 0.001) and dissolved organic C and MWD (R = 0.5600, P < 0.001) indicated that soil aggregation is mainly affected by labile organic C in barren sandy soil. All four types of organic amendments increased SOC content; additionally, ST amendment had the highest capacity for aggregate formation. The results indicated that ST amendment is more appropriate for barren sandy soil than BR, PM or BC amendments, and improves soil quality for sustainable soil management.